Analisis Faktor-Faktor Yang Mempengaruhi Brand Ambassador Blackpink Dan Digital Marketing Terhadap Brand Image Shopee Pada Mahasiswa Program Studi Bisnis Digital Universitas Negeri Medan - Wahyu Hidayat, M; Nugrahadi, Eko Wahyu (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2024)
The popularity of Korean culture in Indonesia is very popular among young people. This opportunity is utilized by many e-commerce players who make K-pop idols their brand ambassadors. This study aims to determine the effect of Blackpink brand ambassadors and digital marketing strategies on Shopee's brand image on students of the Digital Business Study Program at Medan State University. Based on the results of the t test, it is found that the brand ambassador variable has a positive and significant effect on brand image. Digital marketing has a positive and significant effect on brand image. Based on the results of the f test, simultaneously brand ambassadors and digital marketing have a positive and significant effect on brand image. in the determination coefficient test, a value of 0.348 is obtained so that it can be said that 34.8% of the proportion of brand image is influenced by brand ambassadors and digital marketing while the remaining 65.2% is influenced by other variables not examined.